Assessing transport and retention of nitrate and other materials through the riparian zone and stream channel with simulated precipitation. Issue 3 (7th January 2022) - Dodds, Walter K.; Wichman, Gretchen; Guinnip, James P.; Corman, Jessica R.; Blair, John M.
Abstract: Riparian zones, the interfaces between land and stream, perform vital ecosystem functions including transformation and retention of nutrients and sediment moving across the landscape. Although many studies assess transport through and transformation of materials in riparian zones, less is known about the direct influence of precipitation falling on these zones on material retention and transport. Additionally, few experiments can compare riparian retention to stream‐channel retention. We present a novel experimental approach to assess retention of nitrate entering as precipitation in riparian zones and compare riparian retention and movement of nitrate, other ions, sediments to and within the adjacent stream channel. We simulated an intense precipitation event with 15 N‐labelled nitrate as a bioactive solute and bromide as an inert tracer. This method extends tracer release approaches applied to streams worldwide and links it to processes at the aquatic/ terrestrial interface. It further allows determination of movement of materials into streams from bankside precipitation. The riparian zone removed or retained a greater proportion of nitrate than the stream relative to bromide; over half the added bromide reached the stream through a few metres of riparian zone, compared to only 0.2% of the added nitrate. Of the 0.2% that reached the stream, 30% of that nitrate was removed or retained by instream processes after travelling 60 downstream. Roughly 10% of the total 15 N addition ended up sequestered in the above‐ground portions of the riparian grasses by the end of the growing season, and very little of it was recovered from the soil. We saw little evidence of bulk transport of other ions or sediment from this riparian soil to the stream. Our data are consistent with the concept of high nitrate retention in vegetated riparian zones, even for nitrate falling directly upon them in the form of atmospheric deposition in precipitation.